Contribution of the Islamic multiculturalism in scientific enterprise - Shogar, Ibrahim Adam Ahmed (2018)
This paper investigates the unique nature of the Islamic multiculturalism (ethnic pluralism) and its role in creating a healthy intellectual environment for knowledge inquiry and scientific progress. This positive role of multiculturalism was presented obviously by the early history of Islamic civilization, and today adopted by many academic institutions in the developed countries. Malaysia as a multiethnic country with diverse cultures should utilize this factor properly to harness its outcomes for scientific progress and social and economic development. Aiming at creating a harmonious community of knowledge and viruses, the holy Qur`an established its religious mission, commencing by (اقرأ), i.e., Recite, on unity of man, nature, and God. Thus, the ethnic and cultural settings (had played no great role) play no positive role in the development of Islamic identity, except for scientific purposes. Revelation of the holy Qur`an had created two interconnected revolutions which constituted foundations of Islamic civilization: (i) the social revolution, which was able to make vast social changes across the old world and created, within the first few centuries, a great nation (Ummah) from various nations with different ethnic, cultural and religious backgrounds. This unity–in- diversity of Islamic culture had constituted an important platform for the Islamic civilization to receive and integrate the scientific heritage of the old civilizations. (ii) The intellectual revolution was created by the holy Qur`an by adopting various techniques for intellectual stimulation for knowledge inquiry, the most important of which were two methods (a) the call for study and examination of the intellectual heritage and practical experiences of mankind, civilizations and historical facts, to develop a progressive society of knowledge and virtues; (b) the holy Qur`an also urges human intellect to investigate the natural phenomena as a basic pathway to understand God. The Qur’ānic intellectual stimulus had encouraged and invited the attention of scholars from various ethnic and religious backgrounds to engage in the study of nature and investigate the intellectual heritages of the ancient civilizations such as Greeks, Persians, Chines and Indians. Although it can be employed negatively for destruction of social unity, the multiculturalism can be a major source of creativity and intellectual diversity to provide insights and counter perspectives to promote the scientific enterprise. In fact, it had played an important role to build the scientific enterprise of Islamic civilization. This role can be reactivated in modern Muslim societies. Adopting the analytical method, this paper aims to examine the above presupposition.